Capsule Commentaries. - Hendrickson, Harvey S.; Mayper, Alan G.; Howard, Thomas P.; Fortin, Karen A.; Tondkar, Rasoul H.; H. S. H.; Lam, Wai P.; Gaertner, James F.; Prakash, Arun J.; Bannon, Richard J.; Crumbley, D. Larry; Banks, Warren E.; et al. (The Accounting Review, 1985)
Abstract The article discusses several books about various topics. Some of the books are: "Deterring Fraud: The Internal Auditor's Perspective," by W. Steve Albrecht, Ketth R. Howe and Marshall B. Romney, "Management Control in Nonprofit Organizations," 3rd ed., by Robert N. Anthony and David W. Young, "Business Expansion Scheme," by Brian Armitage, "Bank Accounts: A World Guide to Confidentiality," by Edouard Chambost, translated by Peter Walton and Margaret Thompson, "The Tangled Web of Price Variation Accounting: The Development of Ideas Underlying Professional Prescriptions in Six Countries," by F.L. Clarke, "Fore-Runners of Realizable Values Accounting in Financial Reporting," edited by G.W. Dean and M.C. Wells, "Careers in Accounting," by Gloria L. Gaylord and Glenda E. Ried, "Bridges to Infinity: The Human Side of Mathematics," by Michael Guillen, "Bond Duration and Immunization: Early Developments and Recent Contributions," edited by Gabriel A. Hawawini, "Foundations: The Greenwood Encyclopedia of American Institutions," edited Harold M. Keele and Joseph C. Kiger, "The Impact of Taxes on U.S. Citizens Working Abroad," by Ernest R. Larkins.